Weapon-Target Assignment and Firing Scheduling for Rapid Engagement with Heterogeneous Interceptors - Park, Hyeon-Woo; Choi, Han-Lim (International journal of aeronautical and space sciences, 2023)
This paper addresses engagement control of naval fleet with heterogeneous defensive weapons against approaching anti-ship missiles. A combined decision making problem that include weapon-target assignment and firing schedule is considered to decide on which defensive weapons to fire on which targets in what order, taking into account the flight time of heterogeneous defensive weapons, limitations in the launch interval, and the geometric aspects of the incoming targets. A new mixed-integer nonlinear program formulation is presented; then, a mixed-inter linear program approximation on the basis of piecewise linear approximation and McCormick relaxation is proposed for computational tractability. For further efficiency, a greedy algorithm is also presented to deal with a realistic problem. Numerical examples on several representative engagement scenarios demonstrate the validity of the proposed methodology.